Cattle seroprevalence and risk factors associated with bovine viral diarrhea in the northeastern of Colombia (2021)
Bovine viral diarrhea (BVD) is one of the most common and economically significant viral infections in cattle. Different risk factors have been associated with viral exposure and transmission, generating endemic regions with different biotype circulations. To find the BVD status in the northeastern region of Colombia, this study aimed to determine the seroprevalence and risk factors associated with the disease in non-vaccinated farms. For this purpose, a two-time point sampling strategy was developed, obtaining serum from 1157 animals housed in 25 farms distributed in 46 townships, thus for antibody detection against nonstructural protein 3 (NS3, p80) of bovine viral diarrhea virus (BVDV) using an indirect ELISA test. For the first time in Colombia, the presence of serological persistent cattle was evaluated in 1047 animals 3 weeks later of first sampling. The information on a standardized questionnaire with closed and dichotomic answers was used to calculate the putative risk factors. The association analysis by univariate and multivariate logistic regression reported odds ratios (OR) with a 95% of confidence interval (C.I). The overall seroprevalence was 65% (95% CI 62.5–72.9%), with variations according to age ranges. The prevalence of persistent serological positive corresponded to 37.7% (95% CI 34.2–41.5). The risk factors found by multivariate analyses were the lease of pastures (OR = 2.071 CI 1.485–3.690), the use of the same needle (OR = 2.249 CI 1.354–3.736), the molasses supplementation (OR = 2.742 CI 1.156–5.807), and the native Creole breed (OR = 1.895 CI 1.416–2.804). The results of this study confirmed the endemism and higher common exposure to BVDV, as well as the presence of serological persistent cattle in Valledupar, Colombia.